K3 HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU PENGGUNAAN APD PEMANEN KELAPA SAWIT PT. X ROKAN HULU - Yuharika Pratiwi; Azan Fariscy (LPPM Universitas Abdurrab, 2022)
ABSTRACT Personal Protective Equipment (PPE) is a collection of tools used by workers to protect part or all of their bodies from potential hazards or work accidents. Based on data from the International Labor Organization (ILO) 2018 every day more than 2.78 million deaths per year as a result of work accidents or work- related diseases. â€œMeanwhile, based on data from the Badan Penyelenggara Jaminan Sosial (BPJS) for employment in Indonesia in 2018, there were 173,105 cases of work accidentsâ€. The cause of the accident comes from human factors, there are many factors that cause work accidents, including factors of knowledge, attitudes, behavior in using PPE, as well as lack of information related to the risk of work accidents. This study used an analytic observational study design, with a cross sectional study design. The sampling technique was carried out by total sampling and statistically tested using the chi-square test. The purpose of this study was to determine the relationship between knowledge and attitudes with the behavior of using PPE on oil palm harvesters at PT. X Rokan Hulu. The results of this study found that there was a relationship between the knowledge of PPE use and the behavior of using PPE on harvesters (p-value = 0.002), and a relationship between the attitude of using PPE and the behavior of using PPE (p- value = 0.047)